Pengaruh Nilai Tukar terhadap Tingkat Kemiskinan di Indonesia Periode 1986-2024 - Debi Marissa Marpaung; Muhammad Amir Arham; Rifi Fazrina Djuuna (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the long-run effect of the exchange rate on poverty levels in Indonesia during the 1986–2024 period, test the cointegration relationship between the exchange rate and poverty, and identify the transmission mechanism through imported inflation and purchasing power. The data used are annual time series secondary data sourced from the Central Statistics Agency (BPS) and Bank Indonesia (BI). The analytical methods employed include multiple linear regression, Vector Autoregression (VAR), and the Autoregressive Distributed Lag (ARDL) model as the primary method. The Augmented Dickey-Fuller (ADF) stationarity test reveals that the exchange rate variable is stationary at first difference I(1). The long-run ARDL estimation results indicate that the exchange rate has a significant negative effect at the 10 percent level on poverty, with a coefficient of -2.526. This implies that rupiah appreciation tends to reduce poverty through price stability and purchasing power mechanisms. Conversely, currency depreciation raises import prices, drives domestic inflation, and worsens the welfare of poor households. The Bounds Test confirms a long-run cointegration relationship between the exchange rate and poverty. These findings imply that exchange rate stability is an essential prerequisite for effective poverty alleviation policies in Indonesia.